Are You Suggesting That's My Hand? The Relation Between Hypnotic Suggestibility and the Rubber Hand Illusion. (June 2015) - Walsh, E.; Guilmette, D. N.; Longo, M. R.; Moore, J. W.; Oakley, D. A.; Halligan, P. W.; Mehta, M. A.; Deeley, Q.
Hypnotic suggestibility (HS) is the ability to respond automatically to suggestions and to experience alterations in perception and behavior. Hypnotically suggestible participants are also better able to focus and sustain their attention on an experimental stimulus. The present study explores the relation between HS and susceptibility to the rubber hand illusion (RHI). Based on previous research with visual illusions, it was predicted that higher HS would lead to a stronger RHI. Two behavioral output measures of the RHI, an implicit (proprioceptive drift) and an explicit (RHI questionnaire) measure, were correlated against HS scores. Hypnotic suggestibility correlated positively with the implicit RHI measure contributing to 30% of the variation. However, there was no relation between HS and the explicit RHI questionnaire measure, or with compliance control items. High hypnotic suggestibility may facilitate, via attentional mechanisms, the multisensory integration of visuoproprioceptive inputs that leads to greater perceptual mislocalization of a participant's hand. These results may provide insight into the multisensory brain mechanisms involved in our sense of embodiment.